Training on MSME’s Development Strategies in Wooden Painting Crafts (study case Bloomy Wooden Art) - maryani, Maryani; Udiono, Tangkas; Fanthi, Reno; Sofiana, Yunida; Sidharta, Christanto (Bina Nusantara University, 2024)
The variety of works of painting in each region creates high competition between one painter and another in marketing their products. Considering that in the 2000s, the development of the 'fine arts market' in Indonesia experienced very rapid growth, especially in the achievement of works and products. Bloomy Wooden Art is a company (home industry) which operates in the field of painting crafts using wood media which has been shaped into wall decorations, multi-purpose boxes, tissue boxes, trays, glasses, bowls, decorative tables, etc. The painting arts highlighted here are naturalistic such as flowers, fruit and natural beauty along with elements and animals. The aim of the service is to implement the strategy for developing wood painting craft MSMEs in West Jakarta. The method of implementing service is in 3 (three) stages, namely the preparation stage, implementation stage and evaluation stage. Theory in evaluation uses SWOT analysis to determine weaknesses, strengths, threats and opportunities. Based on the results of initial observations, Bloomy Wooden Art painting MSMEs are generally running well, but there are still shortcomings in terms of marketing aspects of wooden painting products using the social media Instagram which are not optimal, the availability of raw materials and supporting equipment and knowledge in the field of marketing.